Peningkatan Hasil Belajar Matematika melalui Media Elevator pada Materi Penjumlahan dan Pengurangan Kelas 1 SD (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to improve mathematics learning outcomes on addition and subtraction material through the use of elevator media in Grade 1 at SDN Pakahan in the 2024/2025 academic year. The problems encountered include low understanding of place value concepts, confusion in the borrowing and carrying process, and monotonous and less varied learning methods. The study employed a classroom action research approach conducted in two cycles, using both quantitative (pre-test and post-test) and qualitative (observation, interviews, and reflective journals) data collection techniques. The results showed an increase in the average student score from 72.2 initially, to 78.8 in the first cycle, and 88.4 in the second cycle, with a learning mastery rate reaching 100%. This improvement was influenced by the use of concrete learning media, increased student motivation, appropriate evaluation questions, and effective classroom management. Thus, the elevator media proved to be effective in enhancing students’ understanding and learning outcomes in basic arithmetic operations.